Entrepreneurship Learning through Pramuka Activity - Dulatip Dulatip; Ifit Novita Sari; Dwi Fita Heriyawati (EDUTEC : Journal of Education And Technology, 2020)
Pramuka is a form of non-formal education that becomes a place in the implementation of Pramuka education. In Pramuka activities, its members are trained with various skills, including leadership, discipline, self-confidence, mutual help, and independence. Its activities are generally carried out in the open with fun, interesting, directed activities by the basic principles and Pramuka methods. In general, Pramuka activities are only filled with the same activities, but in Sudirman Kalipare High School, Malang Regency has innovations for Pramuka as extracurricular activities by incorporating entrepreneurial learning. As a result, students are increasingly honed in their creativity and find a breakthrough to developed into an entrepreneurial venture with low capital and maximum results. Jendral Sudirman High School Scout Contingent won 1st place in the Sangga Putri Business Plan in the Pramuka Achievement Competition in the Bali-Bali Level VIII 2019.